Analisis Aspek Kognitif dalam Komunikasi Buku Tematik Kelas 3 SD/MI - Muhammad Sufyan Ats-Tsauri; Maemonah Maemonah; Ahmad Noviansah (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Human beings as dynamic creatures that are always there is a change in both physical and non-physical changes, physical development of the growth of the life of a child then non-physical in the development of a pattern of participants in both affective cognitive and psychomotor, so that the development of learners as they are discovered in the theory of Piaget is the third-grade students of elementary school is at the operational phase of the state (age 7-11 years), in this stage of development, the development of children will develop the children's knowledge in Taksonmoi Bloom theory which is given to understanding, implementing, analyzing, evaluating, and creating. The research method in this scientific work is the type of research used is qualitative research with a library research method by collecting data from various sources of literature using books, journals, national seminar proceedings, and scientific articles related to the research being conducted. As well as conducting analysis in class III thematic book SD/MI Curriculum 2013. Then, analyse and review related theories. The author presents the data findings objectively and systematically through a descriptive data analysis technique. Qualitative research is a study that presents data in a descriptive analysis through the data analysis needed. Remembering, understanding, implementing, analyzing, evaluating and creating. Thus, from the analysis of the thematic teaching books of class III, MI/SD already relevant to the theory used.